2002
DOI: 10.1007/bf02982797
|View full text |Cite
|
Sign up to set email alerts
|

The Association of HLA Antigen and GVHD in Allogeneic Hemopoietic Stem Cell Transplantation with Histocompatible Sibling Donor: A Single-Center Experience in Korea

Abstract: We analyzed the association of HLA antigens with incidence of organ-specific graft-versus-host disease (GVHD) after allogeneic hemopoietic stem cell transplantation (allo-HSCT) from an HLA-matched sibling donor. We retrospectively reviewed the clinical records of allo-HSCT recipients and found 389 patients who had received matched-sibling HSCT. HLA types, GVHD grades, and the development of acute or chronic GVHD, factors that reflect a certain immunological impact associated with involved organs, were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…HLA-A3 and B7 have been reported to have contrasting effects in different studies. [131415161718192021222324] In our study, we found that HLA-A31 allele was a risk factor for intestinal aGVHD. There have been few researches about the influence of HLA haplotypes on aGVHD; we examined this issue and found that HLA-B40-DR15 and HLA-B46-DR9 haplotypes were risk factors for intestinal aGVHD.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…HLA-A3 and B7 have been reported to have contrasting effects in different studies. [131415161718192021222324] In our study, we found that HLA-A31 allele was a risk factor for intestinal aGVHD. There have been few researches about the influence of HLA haplotypes on aGVHD; we examined this issue and found that HLA-B40-DR15 and HLA-B46-DR9 haplotypes were risk factors for intestinal aGVHD.…”
Section: Discussionsupporting
confidence: 50%
“…HLA loci have also been reported to have impacts on acute graft-versus-host disease (aGVHD),[131415161718192021222324] which is a major complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, the influences of HLA haplotypes on aGVHD have been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the data in this study, showing a relatively lower rate of acute GvHD after haplotype mismatch transplantation, form a basis for population genetics and disease association studies in Korea. 12 Therefore, conditioning regimens in which consideration is given to genetic differences and racial specificity should be evaluated in a larger patient population.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] There have been conflicting reports regarding the relationship between hematopoietic growth factor use (G-CSF and GM-CSF) after HCT and the development of GVHD. A meta-analysis of 18 studies including 1,198 patients failed to reveal differences in the incidence of acute or chronic GVHD in patients who did or did not receive hematopoietic growth factors.…”
Section: )mentioning
confidence: 99%